The Importance of the Drug Noltrex in Osteoarthritis (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Osteoarthritis (OA) is the most common disease of the musculoskeletal system, especially in the elderly, characterized by severe pain and often the presence of inflammatory signs. Upon reaching 75 years of age, OA occurs in 80% of the population. Pain is the most common symptom of OA, so treatment of the disease is aimed primarily at reducing pain and, as a result, improving joint function. Treatment of OA can begin with various non-pharmacological methods, including patient education, physical therapy, transcutaneous stimulation, etc. However, if non-pharmacological treatment methods are insufficiently effective, drug therapy is required. The action of most drugs is aimed primarily at treating the symptoms of the disease, although some of them are considered as drugs that affect the catabolic and anabolic processes that occur when cartilage is damaged. These medications are classified as disease-modifying drugs. The choice of drugs and combinations of various treatment methods remains strictly individual. Knowledge of the mechanisms of action, effectiveness, contraindications when prescribing drugs, and the safety profile of drugs is extremely important. The most common previously used methods for treating osteoarthritis (HA injections, oral chondroprotectors, lavage and debridement) are currently time received critical assessment, reflected in Cochrane reviews. The main conclusions of research analysts are as follows: a) positive effect of injections of HA drugs proven only for therapy for 13 weeks; b) results of treatment of patients with gonarthrosis the three methods mentioned above do not allow talk about their clear clinical effectiveness.